PENINGKATAN KEMAMPUAN MEMBACA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN KARTU HURUF DI TK NEGERI PEMBINA KABUPATEN TANGERANG - Ayundarani, Dwininda; Maulina, Murni (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Based on observations conducted at TK Negeri Pembina in Tangerang Regency, there are several children in group B who have not yet mastered letter recognition, particularly consonants. As a result, they often struggle with assembling and reading words. The aim of this study is to understand the process and results of improving children's reading skills through letter card games. Before the study, young children at TK Negeri Pembina demonstrated a low reading ability at 23%. The method used in this study is action research, conducted in 2 cycles. Cycle I consisted of 8 sessions, but due to the limited improvement in children's reading ability, the study proceeded to cycle II, which comprised 4 sessions. The difference in the number of sessions was due to the children's reading ability showing significant improvement by the fourth session of cycle II, achieving a success rate of 75%. The study involved 10 children as subjects. Data collection techniques included observation, interviews, documentation, and data analysis. The study found that: 1) at the beginning of cycle I, the children's reading ability increased to 46%, and 3) cycle II yielded a result of 76%. Thus, it can be concluded that letter card games can enhance the reading ability of children aged 5-6 years at TK Negeri Pembina in Tangerang Regency.